2016
DOI: 10.1177/0022034516657070
|View full text |Cite
|
Sign up to set email alerts
|

Pain Mechanisms and Centralized Pain in Temporomandibular Disorders

Abstract: Until recently, most clinicians and scientists believed that the experience of pain is perceptually proportional to the amount of incoming peripheral nociceptive drive due to injury or inflammation in the area perceived to be painful. However, many cases of chronic pain have defied this logic, leaving clinicians perplexed as to how patients are experiencing pain with no obvious signs of injury in the periphery. Conversely, there are patients who have a peripheral injury and/or inflammation but little or no pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
122
1
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(139 citation statements)
references
References 63 publications
6
122
1
10
Order By: Relevance
“…Figs 1C and 2C) within TMD are not significant with those subjects removed. These relationships will need to be examined again in larger samples, including TMD patients who have higher levels of clinical pain and more evidence of pain centralization [20]. …”
Section: Discussionmentioning
confidence: 99%
“…Figs 1C and 2C) within TMD are not significant with those subjects removed. These relationships will need to be examined again in larger samples, including TMD patients who have higher levels of clinical pain and more evidence of pain centralization [20]. …”
Section: Discussionmentioning
confidence: 99%
“…Centralized pain can manifest anywhere in the body and in any type of tissue, and is generally more diffuse than nociceptive or neuropathic pain since many of the central gain controls for incoming nociceptive signals that are recognized to be dysregulated in centralized pain patients can affect pain signals from throughout the body, e.g., diffuse noxious inhibitory controls (DNICs) 46. The degree to which pain can be well localized by the patient (centralized pain cannot be as well localized) is another distinguishing factor between nociceptive and centralized pain 2. Other clinical features of centralized pain include hypersensitivity to a variety of painful (e.g., heat, cold, electrical, pressure) and innocuous sensory stimuli (e.g., bright lights, noises, odors), and a myriad of cooccurring CNS‐organized symptoms (e.g., fatigue, sleep difficulties, mood, and memory problems).…”
Section: Mechanisms Of Orofacial Painmentioning
confidence: 99%
“…It is now known that individuals vary widely in their pain sensitivity, and there often is a very poor relationship between the degree of peripheral damage/inflammation within an individual and how much pain he/she is experiencing. This is especially true in subacute or chronic pain conditions, where frequently there is little evidence of ongoing damage or inflammation in the periphery 2. In these cases, intervening in the periphery – as dentists are trained to do – will not alleviate pain, and could actually worsen a person's clinical condition.…”
Section: Introductionmentioning
confidence: 99%
“…The onset and persistence of pain in patients with TMD can be related to an impairment in the manner in which the central nervous system (CNS) receives and processes nociceptive stimuli . Previous research has suggested that these patients show generalised hyperalgesia, structural and functional changes at the cortical level, and increased areas of pain, all of which are compatible with a central sensitisation process . In addition, these types of CNS alterations can lead to a disorder in the processing of somatosensory stimuli, as well as an impairment in tactile acuity …”
Section: Introductionmentioning
confidence: 99%